Kicking and pulling: Are propulsive forces the secret to peak swimming performance? - Hughes, P. A.; Weyand, P. G. (International Journal of Exercise Science Conference Proceedings, 2026)
Although swimming is a widely popular, well-researched global sport, the determinates of maximum sprint swimming forces across the four competitive strokes, and their relation to maximal sprint velocity are not known.